PERKEMBANGAN DAKWAH DI BIDANG POLITIK DAN ILMU PENGETAHUAN PADA MASA DINASTI GHAZNAWI, BUWAIH DAN SALJUK - Muhammad Alim Ihsan (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
From a historical perspective, there are three dynasties in relation to the system of Islamic government. First, Ghaznawite dynasty, settled down in Ghazna, that achieved progress and advancement in the rule of Mahmod al GhaznawL This advancement can be observed from such aspects as politics and science. Secondly, Buwaihite dynasty with its power that cover mostly Iran and Iraq. The significant advancement and progress occurred when Abbasite dynasty had weakened in Baghdad, and when Tughril Beik from Saljuq ruled South Turkey. Thirdly, Saljuq dynasty, which was esbtalished by Saljuq ibn Duqaq from Ghuzz. This dynasty ruled when they overthrown Buwaih dynasty that had ruled at that time. The advancement of Islam in this period occurred when Nizam al-Mulk rule this dynasty. He established the University of Nizamiyyah, which became in tum a model for universities in the future.